2018
DOI: 10.1101/453522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An enriched network motif family regulates multistep cell fate transitions with restricted reversibility

Abstract: Multistep cell fate transitions with stepwise changes of transcriptional profiles are common to many developmental, regenerative and pathological processes. The multiple intermediate cell lineage states can serve as differentiation checkpoints or branching points for channeling cells to more than one lineages. However, mechanisms underlying these transitions remain elusive. Here, we explored gene regulatory circuits that can generate multiple intermediate cellular states with stepwise modulations of transcript… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 103 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…This approach usually only considers the frequency of circuit motifs' appearance, but not their functionality, for initial identification. To address this issue, recent studies 5,6,14,15 have been focused on identifying functionally relevant circuit motifs capable of producing specific dynamical behaviors using mathematical modeling . CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach usually only considers the frequency of circuit motifs' appearance, but not their functionality, for initial identification. To address this issue, recent studies 5,6,14,15 have been focused on identifying functionally relevant circuit motifs capable of producing specific dynamical behaviors using mathematical modeling . CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…19.500691 doi: bioRxiv preprint and then analyzing them for enriched motifs. These types of approaches have been devised and applied to elucidate circuits capable of generating oscillations 16,17,18 and multiple stable steady states 6,19,20 . Ye et al 6 identified three-node circuits capable of generating stepwise transitions between four states with limited reversibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such situations have recently been shown to occur in the multistep transitions in the early T cell lineage commitment. 50 Broken branches are also known to generate unusual bifurcations, such as Isola bifurcation, that were proposed to be relevant in the long term memory 51 and in the neural stem cell development. 52 The proposed potential based method will not face such problem as it determines the steady states based on the local extremum in the potential landscape.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, for more complex networks such dimensional reduction may not always be possible. However, recently Ye et al 50 have investigated network topologies that have the potential to generate irreversible tetrastability with sequential activation of genes, and they found enrichment of certain subnetworks responsible for such behavior in early T cell development. Consistent with our work, the occurrence frequency of MISA motif in these subnetworks, particularly in Type-II, is quite large.…”
Section: ■ Discussionmentioning
confidence: 99%